Effectiveness of fungicides for protection of Catalpa bignonioides against powdery mildew - Булат, А. Г. (Forestry and Forest Melioration, 2024)
Introduction The widespread use of introduced species of the genus Catalpa in landscaping necessitates a comprehensive investigation into phytopathogenic fungal species, disease etiology, and effective plant protection methods. Such research provides valuable insights into the success and future prospects of Catalpa introduction for landscaping and its potential application in other areas of environmental management. Among the fungal pathogens affecting the assimilation apparatus of seedlings and saplings, powdery mildew pathogens (Erysiphales, Ascomycota) warrant particular attention due to their significant impact. The aim of the study was to evaluate the effectiveness of modern fungicides against powdery mildew (Erysiphe catalpae) in catalpa seedlings cultivated in ornamental nursery conditions. Materials and Methods The research, conducted in 2023, assessed the extent of powdery mildew damage in catalpa plantations and evaluated the efficacy of fungicides against Erysiphe catalpae Simonian. Following manufacturer recommendations, seedlings were treated twice – on June 10, and July 20 – using the fungicides Artis Plus, Thalius, and Verben at standard application rates. Results The results demonstrated a significant improvement in plant protection outcomes. Across all experimental variants, an almost complete absence of the powdery mildew pathogen was observed. Disease prevalence decreased from an initial 30–33% to a range of 0.3–1.1% after two treatments. . The overall disease incidence was reduced to 5.5–1.7% in treated seedlings. Based on monitoring data, we confidently confirm the efficacy of the tested fungicides in protecting catalpa seedlings from E. catalpae. Additionally, assessing changes in the biometric parameters of treated seedlings provided insights into their viability, adaptation to pathogens, and potential effects of chemical treatments on plant health. The average height of treated seedlings increased by 64–75% compared to the control, suggesting that the fungicides suppressed pathogen activity and promoted growth by reducing disease pressure. Moreover, no adverse effects on plant diameter parameters were observed, further supporting the conclusion that the selected fungicides are both effective and safe for Catalpacultivation. Conclusions The study demonstrated the effectiveness of the selected fungicides in protecting Catalpa bignonii seedlings from powdery mildew. Among the tested fungicides, Artis Plus provided the highest level of protection. The double treatment effectively reduced disease prevalence and severity, positively influencing the biometric parameters of the plants. These findings highlight the potential of the tested fungicides as reliable tools for managing powdery mildew in Catalpa cultivation. 1 Fig., 4 Tables, 16 Refs.